Does living in major towns favor institutional delivery in Somalia? - Sheikh, Naima Said; Hussein, Ahmed M.; Mohamed, Shukri Said; Gele, Abdi (Frontiers in Global Women's Health, 2024)
Background: In developing countries, institutional delivery is a key proven intervention that reduces maternal mortality and can reduce maternal deaths by approximately 16-33%. In Somalia, only 32% of births are delivered in a health facility with the assistance of a skilled healthcare provider. We aimed to investigate factors hindering women from giving birth at healthcare facilities in major towns in Somalia, where most of the health facilities in the country are concentrated.Methods: A community-based health survey was carried out in 11 major cities in Somalia between October and December 2021. A structured and pretested questionnaire was used to collect data from 430 women who gave birth in the last five years. Women were recruited through convenient sampling. Descriptive statistics were used, and binary and multivariable logistic regression analyses were performed. Adjusted odds ratios (AOR) with 95% CI were estimated to assess the associations.The overall prevalence of institutional delivery was 57%. Approximately 38% of women living in Mogadishu and 53% living in another ten towns give birth at home. Women who had poor knowledge of the importance of health facility delivery had nearly four times higher odds of delivering at home (AOR 3.64 CI: 1.49-8.93). Similarly, those who did not receive antenatal care (AOR 2.5, CI: 1.02-6.39) and those who did not receive a consultation on the place of delivery (AOR 2.15, CI: 1.17 -3.94) were more likely to give birth at home. The reasons for home delivery included financial reasons, the long distance to the health facility, and the fact that it was easier to give birth at home.The study found that home delivery is high in major towns in Somalia and is associated with a lack of understanding of the importance of health facility delivery, not using ANC, and not receiving consultancy about where to give birth. Primary health care should strengthen information, education, and communication activities. Since the health care system in Somalia is overwhelmingly private, the government may consider access to free and within-reach ANC and health facility delivery for women and girls from families who cannot pay the ANC and childbirth delivery cost.